2002
DOI: 10.1038/sj.ijo.0802077
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of fat and fat-free tissue to body mass index in contemporary children and the reference child

Abstract: BACKGROUND: Body mass index (BMI) is widely used to assess the prevalence of childhood obesity in populations, and to infer risk of subsequent obesity-related disease. However, BMI does not measure fat directly, and its relationship with body fatness is not necessarily stable over time. OBJECTIVE: To test the hypothesis that contemporary children have different fatness for a given BMI value compared to the reference child of two decades ago. DESIGN: Comparison of children from Cambridge, UK with the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 26 publications
(30 reference statements)
5
77
0
1
Order By: Relevance
“…Such a hypothesis is not supported by recent evaluations of children's body composition, which showed that contemporary children in general have lower levels of LM than in previous generations. 32 Thus, increases in fatness, especially central fatness, 33 appear to precede the increases in LM that occur in childhood obesity, with much of the apparent increase in LM attributable to increased height, and to changes in hydration and mineral mass that follow increases in weight. 31 It is possible therefore that our finding that early rapid growth was associated with BMI, but not with fatness, may be due to two issues: first, variability in LM may adversely influence the categorisation of obesity; second, diet and activity levels may mediate possible relationships between early hormonal programming and later fatness.…”
Section: Discussionmentioning
confidence: 99%
“…Such a hypothesis is not supported by recent evaluations of children's body composition, which showed that contemporary children in general have lower levels of LM than in previous generations. 32 Thus, increases in fatness, especially central fatness, 33 appear to precede the increases in LM that occur in childhood obesity, with much of the apparent increase in LM attributable to increased height, and to changes in hydration and mineral mass that follow increases in weight. 31 It is possible therefore that our finding that early rapid growth was associated with BMI, but not with fatness, may be due to two issues: first, variability in LM may adversely influence the categorisation of obesity; second, diet and activity levels may mediate possible relationships between early hormonal programming and later fatness.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] The addition of circumferential measures may help to address the major weakness of BMI: its inability to distinguish between elevated adiposity and elevated lean mass. From a public health perspective, the observation that BMI in children and adolescents A Must and SE Anderson from 1987 to B1997 waist circumferences of British children increased more than BMI 33 suggests that surveillance by BMI alone may obscure important changes in body composition 39 at the population level. Prospective studies that demonstrate that the addition of an indirect measure of central adiposity is more tightly linked to obesity-related health consequences than use of BMI-for-age alone would provide some of the justification needed to add further complexity to research applications and to weight-screening recommendations.…”
Section: Looking To the Futurementioning
confidence: 99%
“…14 This approach of normalising outcomes for height rather than body mass represents a more informative way to compare individuals for the two tissue masses that comprise WT, and helps understand many aspects of body composition and its development over time. 15 It is of particular value in epidemiological studies, where variables such as physical activity may impose independent antagonistic effects on FM and FFM.…”
Section: Introductionmentioning
confidence: 99%